Studi Meta Analisis: Blended Learning terhadap Hasil Belajar Kognitif Siswa - Novita, Ayu; Suryani, Yani; Latifah, Sri; Ningrum, Ayu Reza; Hidayah, Nur (UNIVERSITAS INDRAPRASTA PGRI, 2024)
The development of research on blended learning on learning outcomes continues to grow every time, and updating information related to this variable is important. Therefore, researchers used a meta-analysis study to see how much influence blended learning has on student learning outcomes, especially in science subjects at the education level. This research is descriptive quantitative research using a meta-analysis study method. The sample in this study was taken using the purposive sampling technique, the sample was in the form of scientific articles found in the 2017-2021 timeframe on the Scopus and Google Scholar databases. The instrument used in this research is data coding. The data analysis technique used was descriptive statistics. Twenty-two relevant primary studies published in national and international journals during 2017-2021 were analyzed using the meta-analysis method. Hedges equation was selected to determine the effect size obtained through openMEE software, Forest Plot, and Validation of publication bias data obtained through JASP 0.15.0.0 software using regression and rank correlation methods. The results showed that the application of blended learning as a whole had a positive influence and was able to improve cognitive learning outcomes in science and mathematics learning with an effect size of 1.483 (excellent) based on the random effect model. In addition, the level of education and subject matter did not affect the heterogeneous effect size data. This shows that blended learning is one of the best solutions in implementing science and math learning to improve students' cognitive learning outcomes.